Application of limbal protection technique in epithelium-on corneal collagen cross-linking - Meng-Meng Wang (Guoji Yanke Zazhi, 2021)
AIM: To evaluate the clinical effect of a limbus protection technique during epithelium-on corneal collagen cross-linking(Epi-on CXL)for keratoconus treatment.METHODS: Prospectively clinical study. A total of 15 patients(30 eyes)with diagnosed binocular progressive keratoconus were selected and treated with Epi-on CXL in my hospital from Jan. to Dec. 2019, and divided into 2 groups, Limbus-protecting Group and Control Group. The differences in corrected distance visual acuity, astigmatism, Km, thickness at the thinnest point of cornea, postoperative discomfort score, corneal epithelium healing time, and tear breakup time were compared between the two groups pre- and postoperatively.RESULTS: The corrected distance visual acuity and astigmatism were improved at 3mo postoperatively(P<0.05). The thickness at the thinnest point of cornea and the tear breakup time decreased after Epi-on CXL surgeries(P<0.05). No difference was found in parameters of corrected distance visual acuity, astigmatism, Km, thickness at the thinnest point of cornea, tear break up time, and postoperative discomfort sore between the two groups(P>0.05). However, the postoperative corneal epithelium healing time in Limbus-protecting Group was shorter than in Control Group(3.20±0.56d vs 3.73±0.96d, P=0.041).CONCLUSION:This limbal protection technique can reduce the corneal epithelium healing time after Epi-on CXL surgery, which preliminarily shows the feasibility of this technique.